THE ENACTMENT OF ARTICLE 11 OF THE ITALIAN CONSTITUTION: BETWEEN DOMESTIC AND INTERNATIONAL LAW - Zicchittu, Paolo (Pravni zapisi, 2023)
Starting from the recent invasion of Ukraine by the Russian army, this essay reflects on the meaning, scope, and application of Article 11 of the Italian Constitution. In particular, the paper analyzes, from a diachronic perspective, the rejection of war by examining its practical implications and focusing on the interrelationships between constitutional law and international law in defining the concept of war and collective self-defense.
Keywords: Article 11 of Italian Constitution; War in Ukraine; Self-defense; Pacifist principle; Internationalist principle; Principle of solidarity